Two Molecular Plasma-Based Diagnostic Methods to Evaluate Early Infection of Schistosoma japonicum and Schistosomiasis Japonica - Yang Hong; Qinghong Guo; Xue Zhou; Liying Tang; Cheng Chen; Zheng Shang; Kerou Zhou; Zhizhong Zhang; Jinming Liu; Jiaojiao Lin; Bin Xu; Jun-Hu Chen; et al. (Microorganisms, 2023)
The prevalence and infectious intensity of schistosomiasis japonica has decreased significantly in China in the past few decades. However, more accurate and sensitive diagnostic methods are urgently required for the further control, surveillance, and final elimination of the disease. In this study, we assessed the diagnostic efficacy of a real-time fluorescence quantitative PCR (qPCR) method and recombinase polymerase amplification (RPA) combined with a lateral-flow dipstick (LFD) assay for detecting early infections of Schistosoma japonicum and different infection intensities. The sensitivity of the qPCR at 40 days post-infection (dpi) was 100% (8/8) in mice infected with 40 cercariae, which was higher than in mice infected with 10 cercariae (90%, 9/10) or five cercariae (77.8%, 7/9). The results of the RPA–LFD assays were similar, with sensitivities of 55.6% (5/9), 80% (8/10), and 100% (8/8) in mice infected with 5, 10, and 40 cercariae, respectively. In goats, both the qPCR and RPA–LFD assays showed 100% (8/8) sensitivity at 56 dpi. In the early detection of S. japonicum infection in mice and goats with qPCR, the first peak in positivity appeared at 3–4 dpi, when the positivity rate exceeded 40%, even in the low infection, intensity mice. In the RPA–LFD assays, positive results first peaked at 4–5 dpi in the mice, and the positivity rate was 37.5% in the goats at 1 dpi. In conclusion, neither of the molecular methods produced exceptional results for the early diagnosis of S. japonicum infection. However, they were useful methods for the regular diagnosis of schistosomiasis in mice and goats.